2016
DOI: 10.1007/s12650-016-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous PIV/PTV velocimetry technique in a turbulent particle-laden flow

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Experimental observations and numerical simulations of particle settling in homogeneous and isotropic turbulence with a vanishing mean flow velocity have evidenced that the turbulence is to enhance the terminal fall velocity [81][82][83][84][85][86][87][88][89]. However, a few studies reported that the terminal fall velocity reduces in moderately weak turbulence [90][91][92].…”
Section: (B) Effects Of Hindered Settlingmentioning
confidence: 99%
“…Experimental observations and numerical simulations of particle settling in homogeneous and isotropic turbulence with a vanishing mean flow velocity have evidenced that the turbulence is to enhance the terminal fall velocity [81][82][83][84][85][86][87][88][89]. However, a few studies reported that the terminal fall velocity reduces in moderately weak turbulence [90][91][92].…”
Section: (B) Effects Of Hindered Settlingmentioning
confidence: 99%
“…The goal of this work is to simultaneously measure the gas and particle velocities using particle image velocimetry (PIV) and particle tracking velocimetry (PTV), which has been conducted before in incompressible flows. Previous simultaneous PIV/PTV measurements have used dual-camera systems with optical discrimination Elhimer et al (2016) and single-camera systems with image segmentation of raw images Kiger and Pan (2000) to obtain both particle and velocity fields. Using our ultra-high-speed diagnostics systems, we plan to extend the simultaneous PIV/PTV technique to the compressible flow regime.…”
Section: Introductionmentioning
confidence: 99%
“…In the most general case, a two-wavelength illumination and imaging would be necessary to distinguish between the two phases (Elhimer et al, 2017;Poelma et al, 2006). However, in this case the particles are much larger as compared to the flow tracers, and a simple PIV system is sufficient to separate the particles and fluid tracers (Khalitov and Longmire, 2002;Hwang and Eaton, 2006).…”
Section: Introductionmentioning
confidence: 99%